2019
DOI: 10.1016/j.surfcoat.2019.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on the β-phase depletion in MCrAlYs: A modelling and experimental study towards designing new bond coat alloys

Abstract: This paper investigates the effects of varied temperature conditions on the kinetics of β-phase depletion in MCrAlYs by DICTRA diffusion simulations and experimental observations. A commercially available MCrAlY composition and two modelled compositions were examined at temperature regimes of 1000 °C, 1100 °C and 1200 °C. A previously developed temperature-dependent oxidation model was used at the boundary to examine the β-phase depletion kinetics at different temperatures. The oxide growth kinetics and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 57 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…In the initial stage of oxidation, the stress value of prediction was higher than that of the experimentally determined. Since the oxides scale formed under oxidation condition was mainly consisted of α-Al 2 O 3 , which was considered as the most effective protective oxide for the low diffusivity of oxygen and metal ions in its hexagonal close-packed (HCP) structure [47]. In this case, the growth rate of the oxides scale was very low, contributed the difference with the prediction, indicating Equation (10) was not suitable for the short-time oxidation condition.…”
Section: Resultsmentioning
confidence: 99%
“…In the initial stage of oxidation, the stress value of prediction was higher than that of the experimentally determined. Since the oxides scale formed under oxidation condition was mainly consisted of α-Al 2 O 3 , which was considered as the most effective protective oxide for the low diffusivity of oxygen and metal ions in its hexagonal close-packed (HCP) structure [47]. In this case, the growth rate of the oxides scale was very low, contributed the difference with the prediction, indicating Equation (10) was not suitable for the short-time oxidation condition.…”
Section: Resultsmentioning
confidence: 99%
“…It can form a stable protective alumina layer, and its unique composition design can meet specific performance requirements [1][2][3]. The NiCrAlY coating can promote the formation of Al 2 O 3 oxide film with slow growth, uniformity and strong adhesion at service temperature, which acts as a diffusion barrier layer at service temperature [4]. A large number of studies have shown that the oxidation resistance of Ni-rich MCrAlY alloy is better than that of Co-rich MCrAlY alloy under high-temperature oxidation environment.…”
Section: Introductionmentioning
confidence: 99%